Factors Associated with Repeat Blood Donation at the Northern Zone Blood Transfusion Centre in Tanzania. (13th December 2015) - Mauka, Wilhellmuss I.; Mahande, Michael J.; Msuya, Sia E.; Philemon, Rune N.
Abstract : Background and Objective . The aim of this study was to determine factors associated with repeat blood donation. Methods . This was a cross-sectional study carried out among blood donors aged 18–65 years in northern Tanzania. The questionnaire was administered among 454 participants through the phone. Results . Of the 454 participants, the proportion of repeat donation was 63.9%. In the backward logistic regression analysis, the significant predictors were living in Arusha which had lower odds of repeat donation compared to those living in Kilimanjaro. Knowledge of time interval between donations increased odds of repeating donations. High intention increased odds of repeat donation compared to low intention. Altruistic score had minor effect on increasing odds of repeating donation. Conclusion . Repeat blood donation is affected by proximity of donating site, awareness of the blood donation interval, intention to donate, and experience on previous donation. We recommend continuous education concerning blood donors and donation among health workers and society as a whole; this will create awareness on motivational factors for repeat donations.